The Influence of Discipline and Competence on the Performance of North Luwu Police Employees - Fauzan, Muh Fauzan; Kasran, Muhammad; Jusman (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study aims to determine the effect of work discipline and competence on employee performance at the Police Resort in North Luwu. This study uses a quantitative method, the data is in the form of numbers (figures). The research design uses surveys and questionnaires. The population and sample in this study were all employees, totaling 35 employees. The sample determination used the full sampling method. The data obtained were analyzed using multiple linear regression. The results of the analysis show evidence that work discipline and competence simultaneously have a positive and significant effect on employee performance. This study provides practical implications for company management in designing work discipline and competence strategies to improve employee performance.